Gut microbiota is associated with differential metabolic characteristics: A study on a defined cohort of Africans and Chinese - Nizigiyimana, Paul; Xu, Boya; Liu, Lerong; Luo, Liping; Liu, Tingting; Jiang, Meng; Liu, Zehao; Li, Changjun; Luo, Xianghang; Lei, Minxiang (Frontiers in Endocrinology, 2022)
Objective: This study intended to determine the associations between gut microbiota and glucose response in healthy individuals and analyze the connection between the gut microbiome and glucose metabolism-related parameters. Methods: Fecal bacterial composition and anthropometric, body composition, body fat distribution, and biochemical measures were analyzed. A 75g oral glucose tolerance test (OGTT) was given to each participant to investigate changes in glucagon-like peptide 1 (GLP-1), insulin, and glucose. The whole body fat and the regions of interest of local body composition were analyzed using dual-energy x-ray absorptiometry (DEXA) and gut microbiota composition was assessed through variable regions (V3-V4) of the bacterial 16s ribosomal RNA gene using High-throughput sequencing techniques. Spearman correlation analysis was used to evaluate the association between gut microbiota and clinical and metabolic changes. Results: The number of operational taxonomic units (OTUs) demonstrated a reduction in the diversity and composition of gut microbiota associated with enhancing adiposity, dyslipidemia, insulin resistance, and hyperglycemia. The Alpha diversity revealed that microbiota diversity, richness, and composition were higher in the African group and lower in the Chinese group. Principal coordinates analysis (PCoA) plots of Beta diversity showed significant variability in gut microbial community structure between the two groups (P = 0.0009). LEfSe analysis showed that phylum Bacteroidetes was significantly more abundant in the Chinese group, and this group also harbored members of the order Bacteroidales, family Bacteroidaceae and genus Bacteroides. In contrast, the phylum Verrucomicrobia was significantly more prevalent in the African group (all P < 0.05). Concerning species, metastats analysis revealed 8 species in the Chinese group and 18 species in the African group that were significantly abundant. Spearman’s correlation analysis demonstrated that gut microbiota correlated with the factors that related to glucose metabolism. Conclusion: Our data suggest that there is an interaction between gut microbiota, host physiology, and glucometabolic pathways and this could contribute to adiposity and pathophysiology of hyperlipidemia, insulin resistance, and hyperglycemia. These findings provide an important basis for determining the relation between the gut microbiota and the pathogenesis of various metabolic disorders.